A Jewish Childhood in the Muslim Mediterranean A Collection of Stories Curated by Leïla Sebbar - Brozgal, Lia; Glasberg, Rebecca (University of California Press, 2023)
A Jewish Childhood in the Muslim Mediterranean brings together the fascinating personal stories of Jewish writers, scholars, and intellectuals who came of age in lands where Islam was the dominant religion and everyday life was infused with the politics of the French imperial project. Prompted by novelist Leïla Sebbar to reflect on their childhoods, these writers offer literary portraits that gesture to a universal condition while also shedding light on the exceptional nature of certain experiences. The childhoods captured here are undeniably Jewish, but they are also Moroccan, Algerian, Tunisian, Egyptian, Lebanese, and Turkish; each essay thus testifies to the multicultural, multilingual, and multi-faith community into which its author was born. The present translation makes this unique collection available to an English-speaking public for the first time. The original version, published in French in 2012, was awarded the Prix Haïm Zafrani, a prize given by the Elie Wiesel Institute of Jewish Studies to a literary project that valorizes Jewish civilization in the Muslim world. "Expertly introduced and organized, each essay is as beautiful as the next. This wonderful collection offers a distinctive account of how Jews of different countries in the Middle East and North Africa experienced their place in society." - JESSICA MARGLIN, Associate Professor of Religion, Law, and History at the University of Southern California